2020
DOI: 10.1371/journal.ppat.1008240
|View full text |Cite
|
Sign up to set email alerts
|

Viral infection triggers interferon-induced expulsion of live Cryptococcus neoformans by macrophages

Abstract: Cryptococcus neoformans is an opportunistic human pathogen, which causes serious disease in immunocompromised hosts. Infection with this pathogen is particularly relevant in HIV + patients, where it leads to around 200,000 deaths per annum. A key feature of cryptococcal pathogenesis is the ability of the fungus to survive and replicate within the phagosome of macrophages, as well as its ability to be expelled from host cells via a novel nonlytic mechanism known as vomocytosis. Here we show that cryptococcal vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…The authors of this study proposed that the host response to viral infection, rather than the virulence of the virus, stimulates fungal cell expulsion via induction of type-I interferon signaling [82]. This effect of viral coinfection on NLE was not observed in C. albicans infection [82].…”
Section: Non-lytic Exocytosismentioning
confidence: 89%
See 2 more Smart Citations
“…The authors of this study proposed that the host response to viral infection, rather than the virulence of the virus, stimulates fungal cell expulsion via induction of type-I interferon signaling [82]. This effect of viral coinfection on NLE was not observed in C. albicans infection [82].…”
Section: Non-lytic Exocytosismentioning
confidence: 89%
“…For example, coinfection of macrophages with HIV or measles virus enhanced NLE without altering fungal uptake or intracellular proliferation [82]. The authors of this study proposed that the host response to viral infection, rather than the virulence of the virus, stimulates fungal cell expulsion via induction of type-I interferon signaling [82]. This effect of viral coinfection on NLE was not observed in C. albicans infection [82].…”
Section: Non-lytic Exocytosismentioning
confidence: 93%
See 1 more Smart Citation
“…One of the effects of influenza on local immunity is the induction of type I interferon responses, which has a paradoxical effect on macrophages and neutrophils functions, especially on phagocytosis and early killing [ 5 ]. An in vitro study showed that viral infection triggers interferon-induced expulsion of live Cryptococcus neoformans previously phagocyted by macrophages [ 20 ]. This could be a potential triggering factor for reactivation of fungal infections such as coccidioidomycosis.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, coinfection of macrophages with either HIV or measles virus impaired immunity to the fungal pathogen Cryptococcus neoformans in a type I IFN–dependent manner. The mechanism is most unique and results from IFN‐mediated enhancement of vomocytosis, which results in the fungus being vomited back out of the macrophage unharmed 58 . In all, IFNs produced during a primary viral infection appear to enhance susceptibility to secondary bacterial or fungal pathogen invasion.…”
Section: Changes In Cell Signaling Pathwaysmentioning
confidence: 99%